2020
DOI: 10.33545/pathol.2020.v3.i3c.280
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation profile in liver diseases: A study of 250 cases in a tertiary care hospital

Abstract: Introduction:The liver is the cornerstone of the coagulation system. The physiology of blood coagulation is closely linked to liver function as it synthesizes most of the factors of coagulation cascade and fibrinolytic proteins. So it is responsible for regulation of haemostasis. Hepatic disorders are widely present in tropical countries and are responsible for morbidity and mortality. Aims and Objectives: The objective of this study was to evaluate coagulation abnormalities associated with chronic liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In viral hepatitis and obstructive jaundice, 2.5% have mild hypofibrinogenemia, suggesting fibrinogen has little value. 133 Prajapati et al 134 found that coagulation profile can measure hepatic cell activity and detect cellular harm. In advanced liver cirrhosis, liver parenchyma damage lowers coagulation protein production and increases bleeding risk.…”
Section: Biomarkers Of Liver Diseasementioning
confidence: 99%
“…In viral hepatitis and obstructive jaundice, 2.5% have mild hypofibrinogenemia, suggesting fibrinogen has little value. 133 Prajapati et al 134 found that coagulation profile can measure hepatic cell activity and detect cellular harm. In advanced liver cirrhosis, liver parenchyma damage lowers coagulation protein production and increases bleeding risk.…”
Section: Biomarkers Of Liver Diseasementioning
confidence: 99%